Vascular thrombosis in pediatric kidney transplantation: Graft survival is possible with adequate management. Issue 3 (June 2018) - Gander, Romy; Asensio, Marino; Royo, Gloria Fatou; Molino, José Andrés; García, Laura; Madrid, Alvaro; Ariceta, Gema; Lopez, Manuel
Summary: Objective: Vascular thrombosis (VT) in pediatric kidney transplantation (KT) is a dreaded event that leads to graft loss in almost 100% of cases. In recent years, VT has become the most common cause of early graft loss. The aim of this study was to analyze our experience in diagnosis and treatment of VT and the impact of a new management protocol on patient outcome. Methods: We conducted a retrospective study of 176 consecutive KT performed at our institution by the pediatric urology team between January 2000 and December 2015 and identified patients with VT. A protocol of prevention and early detection of VT was introduced in 2012. Results: Out of 176 KT, nine cases of VT were identified (5.1%). The mean recipient age was 5.1 years (SD 4.9 years) and mean weight was 22.28 kg (SD 15.6 kg). Diagnosis was intraoperative in two cases and within the first 24 h after surgery in the remaining seven. Immediate surgical exploration was performed after diagnosis in all. Of the five episodes that occurred before 2012, all developed complete graft ischemia requiring transplantectomy. However, in the four cases diagnosed after 2012, graft perfusion could be restored in three, and abdominal wall closure with a mesh and delayed sequentially closure under ultrasound guidance was performed. With a follow-up of 30, 25, and 20 months, the three recovered grafts are still functioning normally. Conclusions: Increased awareness and the application of a protocol for prevention, detection and treatment of VT in pediatric KT can prevent graft loss. Immediate surgical intervention is mandatory after diagnosis. Avoiding compartment syndrome with delayed sequential closure may be useful to improve graft survival.